1997
DOI: 10.1029/97jc02386
|View full text |Cite
|
Sign up to set email alerts
|

Capture and release of Lagrangian floats by eddies in shear flow

Abstract: Abstract. A mechanism to explain the observed trapping or release of Lagrangian drifters by eddies is proposed, based on an interaction between the eddy circulation and the background flow. Eddies strong in relation to the background have a large "tra• zone" within which particles are constrained to circulate in closed paths about the center, while relatively weak eddies have a smaller trap zone. Particles outside the.trap zone drift freely, while those inside rotate with the eddy. As an eddy is advected by no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…These became immediately trapped in the energetic circulation of the anticyclone or, in one, case ran aground. The transfer of drifters between eddies can be interpreted in terms of the work of Shapiro et al (1997), who found that a lagrangian drifter will remain inside an eddy while positioned within its 'trap zone'. This is defined for the steady state as the area bounded by the last closed streamline or 'separatrix' inside of which every streamline is closed.…”
Section: Coastal Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…These became immediately trapped in the energetic circulation of the anticyclone or, in one, case ran aground. The transfer of drifters between eddies can be interpreted in terms of the work of Shapiro et al (1997), who found that a lagrangian drifter will remain inside an eddy while positioned within its 'trap zone'. This is defined for the steady state as the area bounded by the last closed streamline or 'separatrix' inside of which every streamline is closed.…”
Section: Coastal Circulationmentioning
confidence: 99%
“…This is the region that interacts with the surrounding fluid. If we wished to identify the 'separatrix' (the boundary of the trap zone defined by Shapiro et al, 1997) it would have to be positioned between the inner eddy of Gaussian velocity profile and this outer ring. Clearly, drifters located in the outer ring will exhibit a greater tendency to drift away from the eddy.…”
Section: The Background Flowmentioning
confidence: 99%
“…It is not clear, however, that the beginning or end of looping necessarily indicates formation or destruction events (Shapiro et al 1997). It is possible that these events represent only the capture or release of floats into or out of the eddies.…”
Section: Bathymetrymentioning
confidence: 99%
“…Based on observations and modeling, previous studies have suggested various factors for eddy formation, such as the effect of bottom topography or irregular structure of the coastline (Kim, 2010;Zimmerman, 1981), spatial patterns in the wind field (Chavanne et al, 2002;Hu et al, 2011;Oey, 1996;Oey et al, 2001), shear flows (Shapiro et al, 1997) and the interplay of these factors with stratification and tidal forcing (Takeoka and Murao, 1993;Vethamony et al, 2005). Berman et al (2000) used a wind-driven numerical model to show the existence of a chain of cyclonic and anticyclonic eddies, semi-permanently residing along the main axis of the gulf.…”
Section: Introductionmentioning
confidence: 99%